Inovasi Guru Menciptakan Komunikasi Pembelajaran Yang Sukses Dan Berpengaruh - Arikarani, Yesi; Bulan, Sedayang; Wulandari, Wulandari; Malani, Pipit; Maulidi, Bima (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2023)
A successful and influential teacher is a teacher who can be a good relationship in terms of teaching, communication, and have the best impression on his students if the teacher teaches with full expertise in educating, training, teaching. This study aims to examine teacher innovation in creating successful and influential learning communication. By using qualitative methods of literature or contect review, which is very helpful in providing context and meaning in analyzing the meaning of innovation, successful teacher learning communication. The results of this study illustrate first, teachers innovate, starting from curriculum innovation, understanding innovating and creativity in student learning processes, modalities, developing strategies, methods, learning models and canva application media that create interesting learning and seem effective and efficient. Second, interactive teacher and student communication Messages are conveyed in the form of material or teachings both verbally and non-verbally. Third, teachers who have four competencies. They are pedagogic, professional, personal and social. Successful teachers are professional teachers, teachers who are ready to face the challenges of the times, teachers who are ready to innovate, work and be creative. Teachers who teach expect the value of worship and shape the character of teachers and students.